ANALISA LALU LINTAS TERHADAP KAPASITAS JALAN BRIGJEND SUDIARTO KOTA SEMARANG - Muhammad Asin Zubet; Wawarisa Fistcar; Wahyu Aktorina (Jurnal Teknik Indonesia, 2025)
oad capacity is the ability of a road section to accommodate the ideal flow or volume of traffic in a certain unit of time, which is expressed in the number of vehicles passing a certain road section in one hour. The aim of this research is to determine road traffic performance by calculating passing vehicles, road geometric conditions and environmental conditions. The study carried out in this research was carried out on Jalan Brigjen Sudiarto, Semarang City with the aim of calculating capacity and service levels, namely by conducting a survey (starting at 06.00 - 22.00), the data obtained was traffic volume data. Data processing was carried out using the Guidelines method. Indonesian Road Capacity (PKJI) in 2023 where the degree of saturation (DS) is an indicator of traffic behavior on the Brigjen Sudiarto section, Semarang City. From the results of the survey data processing, the Capacity value for the Brigjend Sudiarto road from Demak to Semarang was obtained with a road capacity of 3,253 pcu/hour (C) and a traffic volume of 3,261 pcu/hour (Q) degree of saturation (DS) 1.00 ITP F (Flow (obstacles, low speed, volume above capacity, often occur/congestion for quite a long time), while the capacity of the Brigjend Sudiarto road from Demak to Semarang is with a road capacity of 3,253 pcu/hour (C) and a traffic volume of 1,210 pcu/ hours (Q) degree of saturation (DS) 0.37 ITP B (Flow is stable, speed is slightly limited by traffic, driver can still freely choose his speed).